Gradient hole structure electrode and preparation method and application thereof
By applying polystyrene spheres of different particle sizes on the surface of the electrode base and performing low-temperature sintering and electroless plating, gradient pore structure electrodes are prepared, which solves the problem of bubble shielding effect in electrolytic water and achieves efficient hydrogen production effect in electrolytic water.
Patent Information
- Application Number
- CN202411012958.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-08-19
AI Technical Summary
During the electrolytic water process, the bubble shielding effect leads to a decrease in the electrode active site, which increases the energy consumption of the electrolytic water and reduces the efficiency, and may trigger side reactions and affect the purity of the product.
The preparation method of gradient pore structure electrode is adopted. By applying polystyrene spheres of different particle sizes on the surface of the electrode substrate and sintering and electroless plating, a gradient pore structure is formed, and an efficient three-phase reaction interface is constructed to reduce the bubble shielding effect.
The overpotential and electrolytic water energy consumption are reduced, the efficiency of electrolytic water hydrogen production is improved, the bubble shielding effect is avoided, and the activity and stability of the electrode is enhanced.
Smart Images

Figure CN120505647A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of hydrogen production by water electrolysis, and relates to a gradient pore structure electrode and a preparation method and application thereof. Background Art
[0002] In industrial alkaline water electrolysis, bubbles generated by electrolysis not only increase solution resistance but also cover active electrode sites, a phenomenon known as the "bubble shielding effect." This effect is particularly pronounced at high current densities, severely impacting electrolysis efficiency and significantly increasing energy consumption.
[0003] First, theoretically, when electrolyzing water, bubbles are generated on the surface of the electrode below the liquid level. These bubbles reduce the effective area of the electrode, thereby increasing the electrode overpotential. This phenomenon will lead to an increase in the decomposition voltage, which means additional energy loss.
[0004] Secondly, when bubbles form on the electrode surface, they hinder the transfer of reactants and products between the electrode surface and the electrolyte solution, which not only reduces the electrolysis efficiency but also may lead to a decrease in the purity of the product.
[0005] In addition, if the bubbles stay on the electrode surface for too long, they may trigger some side reactions, such as corrosion or redox reactions on the electrode surface, which will lead to energy loss and degradation of electrode performance. Summary of the Invention
[0006] In view of this, the present invention provides a gradient pore structure electrode and a preparation method thereof, wherein polystyrene hydrocarbons of different particle sizes are sequentially coated on the surface of a metal substrate such as aluminum foil, nickel mesh or nickel foam using polystyrene polymers of various particle sizes as templates, and then the polystyrene spheres are fixed by low-temperature sintering; followed by electroplating of a metal coating (or metal coating) such as Ni, NiFe, CoFe or NiCoFe by chemical plating, and finally the polystyrene polymer template is removed with ethyl acetate, and the metal substrate is removed with an alkaline solution to obtain a gradient pore structure electrode.
[0007] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions.
[0008] According to a first aspect of the present invention, a method for preparing an electrode with a gradient pore structure is provided, the method comprising the following steps:
[0009] 1) sequentially coating the surface of an electrode substrate with two or more polystyrene particle sizes, and then performing low-temperature sintering to fix the polystyrene on the surface of the electrode substrate, so that the polystyrene serves as a molecular template for preparing the gradient pore structure electrode, thereby obtaining an electrode substrate with the polystyrene molecular template fixed thereon;
[0010] 2) electroplating a metal coating on the surface of the electrode substrate immobilized with the polystyrene molecular template obtained in step 1) by chemical plating to obtain an electrode substrate immobilized with the polystyrene molecular template containing the metal coating;
[0011] 3) De-templating the electrode substrate with the metal coating and the fixed polystyrene molecular template obtained in step 2) using an organic solvent to remove the polystyrene molecular template, and then removing the metal substrate using an alkaline solution to obtain the gradient pore structure electrode.
[0012] In the above-mentioned method for preparing a gradient pore structure electrode, in step 1), the particle size of polystyrene includes a combination of at least two particle sizes of 100nm to 300nm, 300nm to 900nm, 900nm to 1μm and 1μm to 10μm, that is, the polystyrene uses at least two polystyrenes with different particle sizes.
[0013] In the present invention, polystyrene with a variety of different particle sizes is used as a molecular template, and two or more polystyrene beads with particle sizes of 100nm to 300nm, 300nm to 900nm, 900nm to 1μm and 1μm to 10μm are sequentially coated on the surface of an electrode substrate (for example, aluminum foil). The polystyrene beads are then fixed to the surface of the metal substrate by low-temperature sintering, and then a metal coating such as Ni, NiFe, CoFe or NiCoFe is electroplated on the surface of the polystyrene beads by chemical plating. Finally, the template is removed with an organic solvent (for example, ethyl acetate), and the metal substrate is removed with an alkaline solution to obtain a gradient pore structure electrode.
[0014] The present invention constructs a high-efficiency three-phase reaction interface (i.e., a gas-liquid-solid three-phase reaction interface) of the electrode in the field of hydrogen production by electrolysis of water through gradient pores. Gas precipitation, ion transfer and catalytic reaction occur at the three-phase reaction interface, thereby reducing the bubble shielding effect, lowering the overpotential and energy consumption of water electrolysis, and improving the efficiency of hydrogen production by electrolysis of water.
[0015] In the above-mentioned method for preparing the gradient pore structure electrode, in step 1), when two or more polystyrene polymers with different particle sizes are sequentially coated on the surface of the electrode substrate, the specific steps include:
[0016] First, polystyrene polymers with smaller particle sizes are coated on the surface of the electrode substrate, and then polystyrene polymers with larger particle sizes are coated, so that the polystyrene polymers coated on the surface of the electrode substrate present a gradient change in particle size from small to large.
[0017] In the above-mentioned method for preparing the gradient pore structure electrode, in step 1), when two or more polystyrene polymers with different particle sizes are sequentially coated on the surface of the electrode substrate, the specific steps include:
[0018] The surface of the electrode substrate is first coated with a polystyrene polymer with nano-scale particle size.
[0019] In the above-mentioned method for preparing the gradient pore structure electrode, in step 1), the electrode substrate comprises any one of aluminum foil, nickel mesh and nickel foam.
[0020] In the above-mentioned method for preparing the gradient pore structure electrode, in the step 1), the temperature of the low-temperature sintering is 80-110°C.
[0021] In the present invention, controlling the low-temperature sintering temperature facilitates the fixation of polystyrene on the electrode substrate surface, allowing it to serve as a molecular template for preparing gradient pore structure electrodes. If the sintering temperature is too high, the polystyrene polymer will melt and become unable to serve as a molecular template in the preparation of the gradient pore structure electrode, resulting in the failure to prepare a gradient pore structure electrode.
[0022] In the above-mentioned preparation method of the gradient pore structure electrode, in step 2), when electroplating the metal coating on the electrode substrate fixed with the polystyrene molecular template by chemical plating, constant current electroplating is performed using aluminum foil as the cathode and nickel plate as the anode.
[0023] In the above-mentioned method for preparing the gradient pore structure electrode, in step 2), when the metal coating is electroplated on the electrode substrate fixed with the polystyrene molecular template by chemical plating, the preparation method of the electrolyte is as follows:
[0024] The metal salt, boric acid and surfactant are dissolved in water, and the pH value of the system is adjusted to 2.5-3.2 with inorganic acid to obtain an electroplating electrolyte.
[0025] In the above-mentioned method for preparing the gradient pore structure electrode, in the step 2), the metal salt includes sulfate.
[0026] In the above-mentioned method for preparing the gradient pore structure electrode, in step 2), the inorganic acid includes sulfuric acid.
[0027] In the above-mentioned method for preparing the gradient pore structure electrode, in the step 2), the surfactant may be a conventional surfactant in the art, for example, sodium dodecyl sulfate.
[0028] In the above-mentioned preparation method of the gradient pore structure electrode, in the step 2), during the constant current electroplating process, the current density is 8 to 12 mA·cm -2 (For example, 10 mA cm -2 ).
[0029] In the above-mentioned method for preparing the gradient pore structure electrode, in step 2), constant current electroplating is performed for 25 to 40 minutes.
[0030] In the present invention, during the electroless plating process, if the current density is too low, the electroplating efficiency of the metal coating will be reduced. If the current density is too high, the metal coating will not fill the pores between the polystyrene (PS) polymers during the electroplating process, and the strength of the formed metal coating will be poor.
[0031] In the above method for preparing the gradient pore structure electrode, in step 2), the thickness of the metal coating is 2 to 10 μm.
[0032] In the present invention, a metal coating is electroplated on an electrode substrate fixed with a polystyrene polymer template by chemical plating. When the thickness of the metal coating is too thick, the activity of the resulting gradient pore structure electrode will decrease. That is, too thick a metal coating is not conducive to improving the activity of the hydrogen evolution reaction electrode.
[0033] In the above-mentioned method for preparing the gradient pore structure electrode, in the step 2), the metal coating comprises any one of a Ni coating, a NiFe alloy coating, a CoFe alloy coating and a NiCoFe alloy coating.
[0034] In the above-mentioned method for preparing a gradient pore structure electrode, in step 2), when a nickel-iron alloy (NiFe alloy) coating is electroplated on an electrode substrate fixed with a polystyrene molecular template by chemical plating, the electrolyte is prepared as follows:
[0035] Nickel salt, iron salt, boric acid and surfactant are dissolved in water, and the pH value of the system is adjusted to 2.5-3.2 with inorganic acid to obtain an electroplating electrolyte.
[0036] In the above-mentioned method for preparing the gradient pore structure electrode, in step 2), the nickel salt includes nickel sulfate; and the iron salt includes ferrous sulfate.
[0037] In the above-mentioned method for preparing a gradient pore structure electrode, in step 2), when the metal coating is a NiFe alloy coating or a NiCoFe alloy coating, the atomic ratio of Ni and Fe in the metal coating is 1:1 to 10:1, preferably, the atomic ratio of Ni and Fe in the metal coating is 3:1.
[0038] In the present invention, when electroplating nickel-iron alloy (NiFe alloy) coating, the cathode reaction is: Ni 2+ and Fe 2+ The obtained electrons are reduced to metal NiFe alloy, thereby achieving the electroplating of metal NiFe alloy layer on the surface of the aluminum foil.
[0039] In the present invention, a NiFe alloy coating is electroplated on an electrode substrate fixed with a polystyrene polymer template by chemical plating. When the atomic ratio of Ni to Fe in the alloy coating is less than 1 (i.e., Ni:Fe<1), the stability of the resulting gradient pore structure electrode is poor; when the atomic ratio of Ni to Fe in the alloy coating is greater than 10 (i.e., Ni:Fe>10), the activity of the resulting gradient pore structure electrode is poor.
[0040] In the above method for preparing the gradient pore structure electrode, in step 3), the organic solvent is a polar solvent.
[0041] In the above-mentioned method for preparing the gradient pore structure electrode, in step 3), the organic solvent includes at least one polar solvent selected from the group consisting of ethyl acetate, chloroform, and N,N-dimethylformamide.
[0042] In the present invention, ethyl acetate is used as the organic solvent to remove the polystyrene polymer template, which has the advantages of low toxicity and fast removal.
[0043] According to some embodiments of the first aspect of the present invention, in step 3), the alkaline solution includes a KOH solution or a NaOH solution.
[0044] According to a second aspect of the present invention, there is provided an electrode with a gradient pore structure, wherein the electrode with a gradient pore structure is prepared by any one of the above-mentioned preparation methods.
[0045] The above-mentioned gradient pore structure electrode, the material of the gradient pore structure electrode includes at least one metal element among Ni, Fe and Co metal elements, and the gradient pore structure electrode has gradient pores with at least two pore sizes, wherein the innermost side of the gradient pores is a nanoscale pore.
[0046] In the present invention, the innermost part of the gradient pores is a nanoscale pore, the pore size of which is much smaller than the size of the bubbles (micrometer level), so the bubbles cannot stay at the three-phase reaction interface, thus avoiding the shielding effect of the bubbles.
[0047] The above-mentioned gradient pore structure electrode, the material of the gradient pore structure electrode includes any one of Ni metal, NiFe alloy, CoFe alloy and NiCoFe alloy.
[0048] The above-mentioned gradient pore structure electrode, in order of distance from the electrode substrate from near to far, the pore diameters of the gradient pores include a combination of two or more pore diameters of 100nm to 300nm, 300nm to 900nm, 900nm to 1μm and 1μm to 10μm; that is, the gradient pores have at least two gradient pore structures with different pore diameters.
[0049] The above-mentioned gradient pore structure electrode is made of NiFe alloy.
[0050] In the above-mentioned gradient pore structure electrode, the atomic ratio of Ni to Fe in the NiFe alloy is 1:1 to 10:1.
[0051] In the above-mentioned gradient pore structure electrode, the atomic ratio of Ni to Fe in the NiFe alloy is 3:1.
[0052] According to a third aspect of the present invention, there is provided an application of the above-mentioned gradient pore structure electrode as a hydrogen evolution reaction electrode or an oxygen evolution reaction electrode in the field of hydrogen production by alkaline water electrolysis.
[0053] In the present invention, when the gradient pore structure electrode is used as a hydrogen evolution reaction electrode in the field of alkaline water electrolysis for hydrogen production, gas evolution, ion transfer, and catalytic reactions all occur at the three-phase interface. Because the innermost gradient pores of the gradient pore structure electrode are nanoscale pores, much smaller than the size of bubbles (micrometers), bubbles cannot remain at the reaction interface, thus avoiding the bubble shielding effect.
[0054] In the present invention, the above technical features can be freely combined to form a new technical solution without conflicting with each other.
[0055] The above technical solution provided by the embodiment of the present invention has the following advantages over the prior art: the present invention constructs an efficient three-phase reaction interface through gradient pores, reduces the bubble shielding effect, reduces the overpotential (i.e., overpotential) and energy consumption of water electrolysis, and improves the efficiency of hydrogen production by water electrolysis; BRIEF DESCRIPTION OF THE DRAWINGS
[0056] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0057] Figure 1 The figure is a flow chart of the preparation of the gradient pore structure electrode according to the present invention.
[0058] Figure 2 This is a SEM image of the nickel-iron gradient pore structure electrode prepared in Example 1 of the present invention.
[0059] Figure 3 for Figure 2 Magnified image of . DETAILED DESCRIPTION
[0060] To make the purpose, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.
[0061] According to some embodiments of the first aspect of the present invention, a method for preparing an electrode with a gradient pore structure is provided, and the preparation flow chart thereof is as follows: Figure 1 Specifically, the preparation method comprises the following steps:
[0062] 1) sequentially coating the surface of the electrode substrate with two or more polystyrene particle sizes, and then performing low-temperature sintering to fix the polystyrene on the surface of the electrode substrate, so that the polystyrene serves as a molecular template for preparing the gradient pore structure electrode, thereby obtaining an electrode substrate fixed with the polystyrene molecular template; that is, Figure 1 The template shown;
[0063] 2) electroplating a metal coating on the surface of the electrode substrate immobilized with the polystyrene molecular template obtained in step 1) by chemical plating to obtain an electrode substrate immobilized with the polystyrene molecular template containing a metal coating; that is, Figure 1 Plating shown;
[0064] 3) using an organic solvent to remove the template of the electrode substrate with the metal coating fixed with the polystyrene molecular template obtained in step 2) to remove the polystyrene molecular template, and then using an alkaline solution to remove the metal substrate to obtain the gradient pore structure electrode, that is, Figure 1 De-templated and substrate shown.
[0065] According to some embodiments of the first aspect of the present invention, in step 1), the particle size of the polystyrene includes a combination of at least two particle sizes of 100 nm to 300 nm, 300 nm to 900 nm, 900 nm to 1 μm, and 1 μm to 10 μm, that is, the polystyrene uses at least two polystyrenes with different particle sizes.
[0066] In the present invention, polystyrene with a variety of different particle sizes is used as a molecular template, and two or more polystyrene beads with particle sizes of 100nm to 300nm, 300nm to 900nm, 900nm to 1μm and 1μm to 10μm are sequentially coated on the surface of an electrode substrate (for example, aluminum foil). The polystyrene beads are then fixed to the surface of the metal substrate by low-temperature sintering, and then a metal coating such as Ni, NiFe, CoFe or NiCoFe is electroplated on the surface of the polystyrene beads by chemical plating. Finally, the template is removed with an organic solvent (for example, ethyl acetate), and the metal substrate is removed with an alkaline solution to obtain a gradient pore structure electrode.
[0067] The present invention constructs a high-efficiency three-phase reaction interface (i.e., a gas-liquid-solid three-phase reaction interface) in the field of hydrogen production by electrolysis of water through gradient pores. Gas precipitation, ion transfer and catalytic reaction occur at the three-phase reaction interface, thereby reducing the bubble shielding effect, lowering the overpotential and energy consumption of water electrolysis, and improving the efficiency of hydrogen production by electrolysis of water.
[0068] According to some embodiments of the first aspect of the present invention, in step 1), when two or more polystyrene polymers having different particle sizes are sequentially coated on the surface of the electrode substrate, the specific steps include:
[0069] First, polystyrene polymers with smaller particle sizes are coated on the surface of the electrode substrate, and then polystyrene polymers with larger particle sizes are coated, so that the polystyrene polymers coated on the surface of the electrode substrate present a gradient change in particle size from small to large.
[0070] According to some embodiments of the first aspect of the present invention, in step 1), when two or more polystyrene polymers having different particle sizes are sequentially coated on the surface of the electrode substrate, the specific steps include:
[0071] The surface of the electrode substrate is first coated with a polystyrene polymer with nano-scale particle size.
[0072] According to some embodiments of the first aspect of the present invention, in step 1), the electrode substrate comprises any one of aluminum foil, nickel mesh, and nickel foam.
[0073] According to some embodiments of the first aspect of the present invention, in step 1), the temperature of the low-temperature sintering is 80-110° C. (eg, 90° C. or 100° C.).
[0074] In the present invention, controlling the low-temperature sintering temperature facilitates the fixation of polystyrene on the electrode substrate surface, allowing it to serve as a molecular template for preparing gradient pore structure electrodes. If the sintering temperature is too high, the polystyrene polymer will melt and become unable to serve as a molecular template in the preparation of the gradient pore structure electrode, resulting in the failure to prepare a gradient pore structure electrode.
[0075] According to some embodiments of the first aspect of the present invention, in step 2), when electroplating the metal coating on the electrode substrate fixed with the polystyrene molecular template by chemical plating, constant current electroplating is performed using aluminum foil as the cathode and nickel plate as the anode.
[0076] According to some embodiments of the first aspect of the present invention, in step 2), when a metal coating is electroplated on an electrode substrate having a polystyrene molecular template fixed thereon by chemical plating, the electrolyte is prepared as follows:
[0077] A metal salt, boric acid and a surfactant are dissolved in water, and the pH of the system is adjusted to 2.5 to 3.2 (for example, 2.8) with an inorganic acid to obtain an electroplating electrolyte.
[0078] According to some embodiments of the first aspect of the present invention, in step 2), the metal salt includes sulfate.
[0079] According to some embodiments of the first aspect of the present invention, in step 2), the inorganic acid includes sulfuric acid.
[0080] According to some embodiments of the first aspect of the present invention, in step 2), the surfactant may be a conventional surfactant in the art, for example, sodium lauryl sulfate.
[0081] According to some embodiments of the first aspect of the present invention, in step 2), during the constant current electroplating process, the current density is 8 to 12 mA·cm -2 (For example, 10 mA cm -2 ).
[0082] According to some embodiments of the first aspect of the present invention, in step 2), constant current electroplating is performed for 25 to 40 minutes (eg, 30 minutes).
[0083] In the present invention, during the electroless plating process, if the current density is too low, the electroplating efficiency of the metal coating will be reduced. If the current density is too high, the metal coating will not fill the pores between the polystyrene (PS) polymers during the electroplating process, and the strength of the formed metal coating will be poor.
[0084] According to some embodiments of the first aspect of the present invention, in step 2), the thickness of the metal plating layer is 2 to 10 μm (eg, 5 μm or 8 μm).
[0085] In the present invention, a metal coating is electroplated on an electrode substrate fixed with a polystyrene polymer template by chemical plating. When the thickness of the metal coating is too thick, the activity of the resulting gradient pore structure electrode will decrease. That is, too thick a metal coating is not conducive to improving the activity of the hydrogen evolution reaction electrode.
[0086] According to some embodiments of the first aspect of the present invention, in step 2), the metal coating includes any one of a Ni coating, a NiFe alloy coating, a CoFe alloy coating, and a NiCoFe alloy coating.
[0087] According to some embodiments of the first aspect of the present invention, in step 2), when a nickel-iron alloy (NiFe alloy) coating is electroplated on an electrode substrate having a polystyrene molecular template fixed thereon by chemical plating, the electrolyte is prepared as follows:
[0088] Nickel salt, iron salt, boric acid and surfactant are dissolved in water, and the pH of the system is adjusted to 2.5 to 3.2 (for example, 2.8) with an inorganic acid to obtain an electroplating electrolyte.
[0089] According to some embodiments of the first aspect of the present invention, in step 2), the nickel salt includes nickel sulfate; and the iron salt includes ferrous sulfate.
[0090] According to some embodiments of the first aspect of the present invention, in step 2), when the metal coating is a NiFe alloy coating or a NiCoFe alloy coating, the atomic ratio of Ni and Fe in the metal coating is 1:1 to 10:1, preferably, the atomic ratio of Ni and Fe in the metal coating is 3:1.
[0091] In the present invention, when electroplating nickel-iron alloy (NiFe alloy) coating, the cathode reaction is: Ni 2+ and Fe 2+ The obtained electrons are reduced to metal NiFe alloy, thereby achieving the electroplating of metal NiFe alloy layer on the surface of the aluminum foil.
[0092] In the present invention, a NiFe alloy coating is electroplated on an electrode substrate fixed with a polystyrene polymer template by chemical plating. When the atomic ratio of Ni to Fe in the alloy coating is less than 1 (i.e., Ni:Fe<1), the stability of the resulting gradient pore structure electrode is poor; when the atomic ratio of Ni to Fe in the alloy coating is greater than 10 (i.e., Ni:Fe>10), the activity of the resulting gradient pore structure electrode is poor.
[0093] According to some embodiments of the first aspect of the present invention, in step 3), the organic solvent is a polar solvent.
[0094] According to some embodiments of the first aspect of the present invention, in step 3), the organic solvent includes at least one polar solvent selected from the group consisting of ethyl acetate, chloroform, and N,N-dimethylformamide.
[0095] In the present invention, ethyl acetate is used as the organic solvent to remove the polystyrene polymer template, which has the advantages of low toxicity and fast removal.
[0096] According to some embodiments of the first aspect of the present invention, in step 3), the alkaline solution includes a KOH solution or a NaOH solution.
[0097] According to some embodiments of the second aspect of the present invention, a gradient pore structure electrode is provided, and the gradient pore structure electrode is prepared by any one of the above-mentioned preparation methods.
[0098] According to some embodiments of the second aspect of the present invention, the material of the gradient pore structure electrode includes at least one metal element among Ni, Fe and Co metal elements, and the gradient pore structure electrode has gradient pores with at least two pore sizes, wherein the innermost side of the gradient pores is a nanoscale pore.
[0099] In the present invention, the innermost part of the gradient pores is a nanoscale pore, the pore size of which is much smaller than the size of the bubbles (micrometer level), so the bubbles cannot stay at the three-phase reaction interface, thus avoiding the shielding effect of the bubbles.
[0100] According to some embodiments of the second aspect of the present invention, the material of the gradient pore structure electrode includes any one of Ni metal, NiFe alloy, CoFe alloy or NiCoFe alloy.
[0101] According to some embodiments of the second aspect of the present invention, the pore diameters of the gradient pores include, in order from near to far distance from the electrode substrate, a combination of two or more pore diameters of 100nm to 300nm, 300nm to 900nm, 900nm to 1μm and 1μm to 10μm; that is, the gradient pores have at least two gradient pore structures with different pore diameters.
[0102] According to some embodiments of the second aspect of the present invention, the material of the gradient pore structure electrode is NiFe alloy.
[0103] According to some embodiments of the second aspect of the present invention, the atomic ratio of Ni to Fe in the NiFe alloy is 1:1 to 10:1 (for example, 2:1, 3:1, 5:1, 7:1 or 9:1).
[0104] According to some embodiments of the second aspect of the present invention, the atomic ratio of Ni to Fe in the NiFe alloy is 3:1.
[0105] According to a third aspect of the present invention, there is provided an application of the above-mentioned gradient pore structure electrode as a hydrogen evolution reaction electrode and / or an oxygen evolution reaction electrode in the field of hydrogen production by alkaline water electrolysis.
[0106] Example 1
[0107] A method for preparing a gradient pore structure electrode comprises the following steps:
[0108] S1, pretreatment: 200nm and 2μm polystyrene ball powders were spread on the surface of aluminum foil, and then sintered at 110℃ for 30 minutes;
[0109] S2. Electroplating: 8.40 g nickel sulfate hexahydrate (32 mmol), 0.75 g ferrous sulfate heptahydrate (2.7 mmol), 2.00 g boric acid, and 80 mg sodium lauryl sulfate were dissolved in 80.0 g deionized water and the pH was adjusted to 2.8 with H2SO4 to obtain a plating solution for electroplating. A 30 mm × 30 mm aluminum foil was used as the cathode and a nickel plate was used as the anode. The current was 10 mA·cm -2 Constant current electroplating for 30 minutes; the cathode reaction: Ni 2+ and Fe 2+ The electrons are reduced to metallic NiFe alloy, thereby electroplating a metallic NiFe alloy coating on the aluminum foil surface. After the electroplating is completed, the electrode is rinsed with deionized water. A 20mm x 20mm piece is cut from the center of the electroplated nickel-iron alloy electrode (i.e., the electrode with the NiFe alloy coating on the aluminum foil surface) and used as the anode for electrolysis of water. The coating thickness of the nickel-iron alloy electrode is 2 to 10 microns, and the atomic ratio of Ni to Fe in the coating is 3:1.
[0110] S3, template removal: The nickel-iron alloy electrode (aluminum foil containing a NiFe alloy coating) obtained in step S2 is placed in ethyl acetate to remove the polystyrene beads. Then, the electrode is placed in a 1 mol / L KOH solution to remove the aluminum foil, thereby obtaining a nickel-iron gradient pore structure electrode.
[0111] The nickel-iron gradient pore structure electrode prepared in this embodiment has gradient pores with pore diameters of 200 nm and 2 μm, wherein the pore diameter of 200 nm is located on the inner side of the gradient pores, that is, on the side close to the aluminum foil electrode substrate. Figure 2 and Figure 3 The scanning electron microscope (SEM) images of the nickel-iron gradient pore structure electrode prepared in this example at different microscopic scales are shown.
[0112] Example 2
[0113] A method for preparing a gradient pore structure electrode comprises the following steps:
[0114] S1. Pretreatment: 500 nm and 2 μm polystyrene ball powders were spread on aluminum foil respectively, and then sintered at 110 degrees for 30 minutes.
[0115] S2. Electroplating: 8.40 g nickel sulfate hexahydrate (32 mmol), 0.75 g ferrous sulfate heptahydrate (2.7 mmol), 2.00 g boric acid, and 80 mg sodium lauryl sulfate were dissolved in 80.0 g deionized water and the pH was adjusted to 2.8 with H2SO4 to obtain a plating solution for electroplating. A 30 mm × 30 mm aluminum foil was used as the cathode and a nickel plate was used as the anode. The current was 10 mA·cm -2 Constant current electroplating for 30 minutes; the cathode reaction: Ni 2+ and Fe 2+ The electrons are reduced to metallic NiFe alloy, thereby electroplating a metallic NiFe alloy coating on the aluminum foil surface. After the electroplating is completed, the electrode is rinsed with deionized water. A 20mm x 20mm piece is cut from the center of the electroplated nickel-iron alloy electrode (i.e., the electrode with the NiFe alloy coating on the aluminum foil surface) and used as the anode for electrolysis of water. The coating thickness of the nickel-iron alloy electrode is 2 to 10 microns, and the atomic ratio of Ni to Fe in the coating is 3:1.
[0116] S3, template removal: The nickel-iron alloy electrode (aluminum foil containing a NiFe alloy coating) obtained in step S2 is placed in ethyl acetate to remove the polystyrene beads. Then, the electrode is placed in a 1 mol / L KOH solution to remove the aluminum foil, thereby obtaining a nickel-iron gradient pore structure electrode.
[0117] The nickel-iron gradient pore structure electrode prepared in this embodiment has gradient pores with pore diameters of 500 nm and 2 μm, wherein the pore diameter of 500 nm is located on the inner side of the gradient pores, that is, on the side close to the aluminum foil electrode substrate.
[0118] Example 3
[0119] A method for preparing a gradient pore structure electrode comprises the following steps:
[0120] S1. Pretreatment: 1 μm and 2 μm polystyrene ball powders were spread on aluminum foil respectively, and then sintered at 110 degrees for 30 minutes.
[0121] S2. Electroplating: 8.40 g nickel sulfate hexahydrate (32 mmol), 0.75 g ferrous sulfate heptahydrate (2.7 mmol), 2.00 g boric acid, and 80 mg sodium lauryl sulfate were dissolved in 80.0 g deionized water and the pH was adjusted to 2.8 with H2SO4 to obtain a plating solution for electroplating. A 30 mm × 30 mm aluminum foil was used as the cathode and a nickel plate was used as the anode. The current was 10 mA·cm -2 Constant current electroplating for 30 minutes; the cathode reaction: Ni 2+ and Fe 2+The electrons are reduced to metallic NiFe alloy, thereby electroplating a metallic NiFe alloy coating on the aluminum foil surface. After the electroplating is completed, the electrode is rinsed with deionized water. A 20mm x 20mm piece is cut from the center of the electroplated nickel-iron alloy electrode (i.e., the electrode with the NiFe alloy coating on the aluminum foil surface) and used as the anode for electrolysis of water. The coating thickness of the nickel-iron alloy electrode is 2 to 10 microns, and the atomic ratio of Ni to Fe in the coating is 3:1.
[0122] S3, template removal: The nickel-iron alloy electrode (aluminum foil containing a NiFe alloy coating) obtained in step S2 is placed in ethyl acetate to remove the polystyrene beads. Then, the electrode is placed in a 1 mol / L KOH solution to remove the aluminum foil, thereby obtaining a nickel-iron gradient pore structure electrode.
[0123] The nickel-iron gradient pore structure electrode prepared in this embodiment has gradient pores with pore diameters of 1 μm and 2 μm, wherein the pore diameter of 1 μm is located on the inner side of the gradient pores, that is, on the side close to the aluminum foil electrode substrate.
[0124] Example 4
[0125] The nickel-iron gradient pore structure electrode prepared in Example 1 was used as the anode and cathode in the electrolysis of water to produce hydrogen, respectively. 30% KOH solution was used as the electrolyte. The electrolyte was 80°C, 600 mA / cm 2 The cell voltage of the nickel-iron gradient pore structure electrode in hydrogen production by water electrolysis was measured at a current density of 0.0447 W / m. The results are shown in Table 1.
[0126] Example 5
[0127] The nickel-iron gradient pore structure electrode prepared in Example 2 was used as the anode and cathode in the electrolysis of water to produce hydrogen, respectively. 30% KOH solution was used as the electrolyte. The electrolyte was 80°C, 600 mA / cm 2 The cell voltage of the nickel-iron gradient pore structure electrode in hydrogen production by water electrolysis was measured at a current density of 0.0447 W / m. The results are shown in Table 1.
[0128] Example 6
[0129] The nickel-iron gradient pore structure electrode prepared in Example 1 was used as the anode in the electrolysis of water to produce hydrogen, and a blank nickel mesh was used as the cathode. 30% KOH solution was used as the electrolyte. The electrolyte was 80°C, 600 mA / cm 2 The cell voltage of the nickel-iron gradient pore structure electrode in hydrogen production by water electrolysis was measured at a current density of 0.0447 W / m. The results are shown in Table 1.
[0130] Example 7
[0131] The nickel-iron gradient pore structure electrode prepared in Example 1 was used as the cathode in the electrolysis of water to produce hydrogen, and a blank nickel mesh was used as the anode. 30% KOH solution was used as the electrolyte. The electrolyte was 80°C, 600 mA / cm 2 The cell voltage of the nickel-iron gradient pore structure electrode in hydrogen production by water electrolysis was measured at a current density of 0.0447 W / m. The results are shown in Table 1.
[0132] Example 8
[0133] The nickel-iron gradient pore structure electrode prepared in Example 3 was used as the anode and cathode in the electrolysis of water to produce hydrogen, respectively. 30% KOH solution was used as the electrolyte. The electrolyte was 80°C, 600 mA / cm 2 The cell voltage of the nickel-iron gradient pore structure electrode in hydrogen production by water electrolysis was measured at a current density of 0.0447 W / m. The results are shown in Table 1.
[0134] Comparative Example 1
[0135] Blank nickel mesh was used as anode and cathode in water electrolysis to produce hydrogen. 30% KOH solution was used as electrolyte at 80℃ and 600mA / cm 2 The cell voltage of the nickel-iron gradient pore structure electrode in hydrogen production by water electrolysis was measured at a current density of 0.0447 W / m. The results are shown in Table 1.
[0136] Table 1 Cell voltage of various electrodes in hydrogen evolution reaction in Examples 4-8 and Comparative Example 1
[0137]
[0138] As can be seen from Table 1, the nickel-iron gradient pore structure electrode prepared using the technical solution of the present invention has significant advantages over the traditional nickel mesh electrode. This is mainly because the gradient pore structure electrode not only increases the reactive area but also reduces the bubble shielding effect. In addition, comparing the application effects of the gradient pore structure electrode in Examples 4, 5, and 8, when the inner pore diameter of the gradient electrode is smaller (Example 4), bubble shielding can be prevented, which can effectively reduce the cell voltage and energy consumption.
Claims
1. A method for preparing a gradient pore structure electrode, characterized in that: The preparation method comprises the following steps: 1) sequentially coating the surface of an electrode substrate with two or more polystyrene particle sizes, and then performing low-temperature sintering to fix the polystyrene on the surface of the electrode substrate, so that the polystyrene serves as a molecular template for preparing the gradient pore structure electrode, thereby obtaining an electrode substrate with the polystyrene molecular template fixed thereon; 2) electroplating a metal coating on the surface of the electrode substrate immobilized with the polystyrene molecular template obtained in step 1) by chemical plating to obtain an electrode substrate immobilized with the polystyrene molecular template containing the metal coating; 3) De-templating the electrode substrate with the metal coating and the fixed polystyrene molecular template obtained in step 2) using an organic solvent to remove the polystyrene molecular template, and then removing the metal substrate using an alkaline solution to obtain the gradient pore structure electrode.
2. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 1), the particle size of the polystyrene comprises a combination of at least two particle sizes of 100 nm to 300 nm, 300 nm to 900 nm, 900 nm to 1 μm, and 1 μm to 10 μm.
3. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 1), polystyrene polymers with smaller particle sizes are first coated on the surface of the electrode substrate, and then polystyrene polymers with larger particle sizes are coated, so that the polystyrene polymers coated on the surface of the electrode substrate present a gradient change in particle size from small to large.
4. The method for preparing a gradient pore structure electrode according to claim 3, wherein: In the step 1), the surface of the electrode substrate is first coated with a polystyrene polymer with nano-scale particle size.
5. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 1), the electrode substrate includes any one of aluminum foil, nickel mesh and nickel foam.
6. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 1), the temperature of the low-temperature sintering is 80-110°C.
7. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 2), when electroplating the metal coating on the electrode substrate fixed with the polystyrene molecular template by chemical plating, constant current electroplating is performed with aluminum foil as the cathode and nickel plate as the anode.
8. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 2), when a metal coating is electroplated on an electrode substrate fixed with a polystyrene molecular template by chemical plating, the preparation method of the electrolyte is as follows: The metal salt, boric acid and surfactant are dissolved in water, and the pH value of the system is adjusted to 2.5-3.2 with inorganic acid to obtain an electroplating electrolyte.
9. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 2), the metal salt includes sulfate, and the inorganic acid includes sulfuric acid.
10. The method for preparing a gradient pore structure electrode according to claim 7, wherein: In the step 2), the current density during the constant current electroplating process is 8 to 12 mA·cm -2 The electroplating time is 25 to 40 minutes, and the thickness of the metal coating is 2 to 10 μm.
11. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 2), the metal coating includes any one of a Ni coating, a NiFe alloy coating, a CoFe alloy coating and a NiCoFe alloy coating.
12. The method for preparing a gradient pore structure electrode according to claim 11, wherein: In the step 2), when the metal coating is a NiFe alloy coating, the atomic ratio of Ni to Fe in the metal coating is 1:1 to 10:
1.
13. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 3), the organic solvent includes at least one of ethyl acetate, chloroform and N,N-dimethylformamide.
14. The method for preparing a gradient pore structure electrode according to claim 1, wherein: In the step 3), the alkaline solution includes a KOH solution or a NaOH solution.
15. A gradient pore structure electrode, characterized in that: The gradient pore structure electrode is prepared by the preparation method of the gradient pore structure electrode according to any one of claims 1-14.
16. The gradient pore structure electrode according to claim 15, characterized in that: The material of the gradient pore structure electrode includes at least one metal element selected from Ni, Fe and Co. The gradient pore structure electrode has gradient pores of at least two pore sizes, wherein the innermost side of the gradient pores is a nanoscale pore.
17. The gradient pore structure electrode according to claim 16, characterized in that: The material of the gradient pore structure electrode includes any one of Ni metal, NiFe alloy, CoFe alloy and NiCoFe alloy.
18. The gradient pore structure electrode according to claim 16, characterized in that: In order of distance from the electrode substrate from near to far, the pore diameters of the gradient pores include a combination of two or more pore diameters of 100nm to 300nm, 300nm to 900nm, 900nm to 1μm and 1μm to 10μm.
19. The gradient pore structure electrode according to claim 17, characterized in that: The material of the gradient pore structure electrode is NiFe alloy, and the atomic ratio of Ni to Fe in the NiFe alloy is 1:1 to 10:
1.
20. Use of the gradient pore structure electrode according to any one of claims 15 to 19 as a hydrogen evolution reaction electrode or an oxygen evolution reaction electrode in the field of hydrogen production by alkaline water electrolysis.
Citation Information
Patent Citations
Preparation method of metal grid membrane
CN108103534A
Nickel-based hydrogen evolution electrode material and preparation method thereof
CN108239774A
Ordered porous cobalt-sulfur modified electrode and preparation method and application thereof
CN112834586A
Preparation method of porous titanium-based lead dioxide electrode
CN114016065A
Nickel-molybdenum-iron hydrogen evolution electrode with ordered porous structure, preparation method and application
CN114250485A
Cited By
Multi-scale gradient coupled proton exchange membrane fuel cell catalyst layer water retention structure and preparation method thereof
CN122025666A